DEVELOPMENT OF MOBILE APPLICATIONS AND THEIR ROLE IN MODERN ELECTRONIC COMMUNICATIONS - BIGANYCH, VASYL; SHUSTA, VOLODYMYR; YEVYCH, MARIANNA; SUSLA, ANATOLIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is devoted to the study of the development of mobile applications as an integral part of modern electronic communications. The purpose of the study is to analyze the functional features of mobile applications, evaluate their impact on electronic interaction, and identify key challenges in ensuring data security and compliance with ethical standards in their operation. The study employs a comprehensive methodological approach, including analytical and comparative analysis, to generalize the role and functions of mobile applications across different domains of application. The results demonstrate the growing influence of mobile applications in shaping user experiences and their critical role in communication, healthcare, education, and business environments. Particular attention is paid to the issue of cybersecurity risks associated with mobile application use, as well as the necessity for transparent practices and adherence to ethical standards in their development and functioning. The scientific novelty lies in identifying emerging trends in mobile application development and exploring mechanisms to improve their security and functionality. Theoretical significance is reflected in the generalization of knowledge about the functions and risks of mobile applications, while practical relevance is demonstrated in the proposal of recommendations for developers to enhance user trust and satisfaction. Based on the analysis, it becomes obvious that mobile applications play an increasingly important role in the modern digital world, being not only a means of communication, but also a powerful tool for solving global challenges. As the statistics reviewed show, their development not only contributes to the growth of interaction between users, but also creates new opportunities for improving business processes, increasing the efficiency of communications and strengthening cybersecurity.